Public Awareness and Legal Compliance with the Implementation of Public Order Policies in Bagan Batu, Rokan Hilir: A Syariah Law Perspective - Nasution, Putri Ramadayanti; Sari, Seva Maya (IHSA Institute, 2025)
This study examines the legal awareness and compliance of the public regarding public order policies in Bagan Batu, Rokan Hilir, based on Regional Regulation No. 3 of 2014, using a juridical-empirical legal approach and the perspective of siyasah syar'iyah. The findings indicate that public legal awareness remains pragmatic and has not been fully internalized into consistent legal behavior. Violations committed by street vendors are largely driven by economic hardship, institutional weaknesses, and the absence of viable relocation alternatives. The author critically argues that policies lacking justice and public benefit fail to gain social legitimacy. From the perspective of siyasah syar'iyah, legal obedience must be built on the principles of justice ('adl), public interest (maslahah), and participatory governance (sh?r?). Qur'an Surah An-Nisa (4):59 and Imam al-Mawardi's views assert that obedience to government is conditional upon the fairness and benefit of its policies. Therefore, strengthening legal awareness requires institutional reform, legal education, and the formulation of just and inclusive policies based on Islamic ethical governance